The Contribution of Asung Daya BUMDes in Increasing Village Original Income (PADes) Jatijajar, Bergas District, Semarang Regency - Rahmawati, Esa Mara; Tijan, Tijan; Susanti, Martien Herna; Saputro, Iwan Hardi (Universitas Negeri Semarang, 2023)
Village-Owned Enterprises (BUMDes) are government efforts to create independent and prosperous village communities by relying on the management of the original economic potential in each village. The Jatijajar Village Government took the initiative to form Asung Daya BUMDes as an effort to manage the village's original economic potential so that it can increase Village Original Income (PADes) by utilizing the available original economic potential. This study aims to find out how the contribution of Asung Daya BUMDes in increasing the Village Original Income (PADes) of Jatijajar Village through the role of BUMDes according to Prasetyo in (A. E. Kurniawan, 2016). This research uses qualitative methods and data collection techniques are carried out by interviews, observation, and documentation. The results of this study show that Asung Daya BUMDes have contributed to the increase in Jatijajar PADes. The contribution is made every year by donating as much as 39% of its annual income and can contribute positively in various aspects such as improving the community's economy, community welfare, and public facilities in the village. Even so, there are still some obstacles caused by the lack of employees in the management of Asung Daya BUMDes due to the lack of community participation. This is also caused by public perception that one business unit can interfere with the income of people who have a business. Even so, Asung Daya BUMDes can be a promising solution for improving the economy of villages and communities in them.